2020
DOI: 10.1136/jnnp-2020-324418
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, predictors and prognosis of incidental intracranial aneurysms in patients with suspected TIA and minor stroke: a population-based study and systematic review

Abstract: IntroductionUnruptured intracranial aneurysms (UIAs) are common incidental imaging findings, but there are few data in patients with transient ischaemic attack (TIA)/stroke. The frequency of UIA might be higher due to shared risk factors, but rupture risk might be reduced by intensive secondary prevention. We determined the prevalence and prognosis of UIA in patients with suspected TIA/minor stroke.MethodsAll patients referred to the population-based Oxford Vascular Study (2011–2020) with suspected TIA/minor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Furthermore, ischemic stroke was also found to be associated with a reduced rupture risk in this study. Similar to this finding, a large population-based cohort study 39 reported that the rupture risk of intracranial aneurysms is 2.3 per 1000 person-year among patients with confirmed transient ischemic attack/stroke, which is far lower than that in general population (7.8 per 1000 person-year) reported by Greving et al 3 On the one hand, patients with ischemic stroke have a higher opportunity to undergo angiography imaging screening, resulting in an early detection of incidental unruptured intracranial aneurysms. Subsequently, the guideline-based monitoring on the aneurysms would be certainly initiated in the early phase, which has a positive impact on the outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, ischemic stroke was also found to be associated with a reduced rupture risk in this study. Similar to this finding, a large population-based cohort study 39 reported that the rupture risk of intracranial aneurysms is 2.3 per 1000 person-year among patients with confirmed transient ischemic attack/stroke, which is far lower than that in general population (7.8 per 1000 person-year) reported by Greving et al 3 On the one hand, patients with ischemic stroke have a higher opportunity to undergo angiography imaging screening, resulting in an early detection of incidental unruptured intracranial aneurysms. Subsequently, the guideline-based monitoring on the aneurysms would be certainly initiated in the early phase, which has a positive impact on the outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of intracranial aneurysms was 1.8–3.0% in the general population ( 1 , 5 , 17 ). A previous study reported that the prevalence of UIA was higher among those with transient ischemic attack or minor stroke than in the general population ( 13 ), and the prevalence was as high as 5%. However, among the local population in Hong Kong, the prevalence of UIA among residents with immediate family members suffering from aneurysmal SAH was 2.3% ( 18 ).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, stroke patients will have a higher burden of unruptured intracranial aneurysms (UIA). At present, studies on UIA have shown that the risk of intracranial aneurysms is 70% higher in stroke patients than in the normal population ( 12 , 13 ), and a family history of stroke has been identified as an independent risk factor for UIA ( 12 ). However, there is no study on the prevalence and risk factors for UIA in those with a family history of stroke in China.…”
Section: Introductionmentioning
confidence: 99%
“…Based on available evidence, the baseline prevalence of incidental intracranial aneurysm was estimated at 2% [6]. A sample size calculation determined that for a desired precision of 1% and a corresponding 95% confidence interval, we required a sample size of 1064 patients.…”
Section: Discussionmentioning
confidence: 99%
“…This may be driven by awareness of the risks associated with interventions resulting from the discovery of a new and possibly inconsequential aneurysm. However, notwithstanding the fact that any aneurysm detected incidentally is at risk of subsequent rupture [6], the background rate of aneurysms in an ED population is likely overestimated. Unfortunately, the published data on the background rate of aneurysms is based largely on cadaveric studies, invasive angiography, and magnetic resonance angiography (MRA) and therefore may not reflect the true incidence of incidental aneurysms that would be identified through CTA [7].…”
Section: Introductionmentioning
confidence: 99%